Rising tides [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Chesapeake Bay saga., 1998)
Of three brothers, it was Ethan who shared his father's passion for the Maryland shore. With his father gone, Ethan is determined to make the family boatbuilding business a success, but amidst his achievements lie the most important challenges of his life. There is young Seth, who needs him more than ever. A woman he has always loved but never believed he could have. Ethan must learn to see around his dark and painful past and accept who he is.